Impulsive differential equations - Samojlenko, Anatolij M. 1938-2020 (World Scientific series on nonlinear science. Series A, 1995)
This monograph, written by the representatives of the Kiev school of Nonlinear Mechanics, contains a sufficiently complete study of systems of impulsive linear differential equations, as well as worked out nontrivial examples which could serve as guidelines for solving other particular applied problems